Lessons learned from organizing and teaching virtual phylogenetics workshops - Barido-Sottani, Joëlle; Justison, Joshua A.; Borges, Rui; Brown, Jeremy M.; Dismukes, Wade; do Rosario Petrucci, Bruno; Guimarães Fabreti, Luiza; Höhna, Sebastian; Landis, Michael J.; Lewis, Paul O.; May, Michael R.; Mendes, Fábio K.; et al. (Bulletin of the Society of Systematic Biologists, 2022)
No abstract available.